Redesain Sport Center Gor Debes di Kabupaten Tabanan dengan Menerapan Konsep Arsitektur Kontemporer : bahasa indonesia - I Putu Wikan Pithamaha; Ni Putu Ratih Pradnyaswari Anasta Putri; I Nengah Sinarta; I Wayan Wirya Sastrawan; Putu Siskha Pradnyaningrum (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
The limitations of facilities and infrastructure have hindered the ability of sports in Tabanan Regency to achieve good performance at both regional and national levels. In addition, the lack of attention to the welfare of high-performing athletes has caused some athletes to choose to move elsewhere. From these issues, it is suggested to improve the existing sports facilities and infrastructure in Tabanan Regency through redesign. A Sport Center can be a sports building that accommodates sports activities including training, recreation, and competitions. This research is a qualitative descriptive research with data collection methods in the form of observation and literature study.The application of contemporary architecture that aims to be introduced in the redesign project of the sports center is a style of architecture that does not abandon traditional values but can appear modern according to the times. The application of contemporary architecture in the redesign of the Sports Center in Tabanan will be implemented in aspects of form, materials, aesthetics, circulation, and space.